The effects of Cstb duplication on APP/amyloid-β pathology and cathepsin B activity in a mouse model. - Yixing Wu (Public Library of Science (PLoS), 2021)
People with Down syndrome (DS), caused by trisomy of chromosome 21 have a greatly increased risk of developing Alzheimer's disease (AD). This is in part because of triplication of a chromosome 21 gene, APP. This gene encodes amyloid precursor protein, which is cleaved to form amyloid-β that accumulates in the brains of people who have AD. Recent experimental results demonstrate that a gene or genes on chromosome 21, other than APP, when triplicated significantly accelerate amyloid-β pathology in a transgenic mouse model of amyloid-β deposition. Multiple lines of evidence indicate that cysteine cathepsin activity influences APP cleavage and amyloid-β accumulation. Located on human chromosome 21 (Hsa21) is an endogenous inhibitor of cathepsin proteases, CYSTATIN B (CSTB) which is proposed to regulate cysteine cathepsin activity in vivo. Here we determined if three copies of the mouse gene Cstb is sufficient to modulate amyloid-β accumulation and cathepsin activity in a transgenic APP mouse model. Duplication of Cstb resulted in an increase in transcriptional and translational levels of Cstb in the mouse cortex but had no effect on the deposition of insoluble amyloid-β plaques or the levels of soluble or insoluble amyloid-β42, amyloid-β40, or amyloid-β38 in 6-month old mice. In addition, the increased CSTB did not alter the activity of cathepsin B enzyme in the cortex of 3-month or 6-month old mice. These results indicate that the single-gene duplication of Cstb is insufficient to elicit a disease-modifying phenotype in the dupCstb x tgAPP mice, underscoring the complexity of the genetic basis of AD-DS and the importance of multiple gene interactions in disease.